Technical activity profile and influence of body anthropometry in male elite team handball players - Michalsik, L. B.; Aagaard, P.; Madsen, K. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The present study showed that modern male elite Team Handball (TH) is a physically demanding game characterized by a high number of short-term, high-intense technical playing actions, which are performed intermittently throughout the entire match. Findings indicated that temporary fatigue may occur. Physical demands differed between playing positions. Body anthropometry seems to have an important influence on playing performance at the various playing positions.